(3QHj GdHUjQs - (3GOGf, YGFTIs; (3GdZGfe, MhQs; (3YcGhj, QMGHs; (3cfYGf, CMeOs ((3GdOGQ GdHjVGA, GdeZQHs (3OGQ GdKbGaI ddfTQ hGdJhRjYs, 2024)
(3Gddg gh GdPj jNdb LejY GdcGFfGJ GdcHjQI hGdUZjQI(B. (3Gddg jQGfG LejYkG aj cd ecGf, haj cd hbJ, dCfg GdHUjQ, Cj Cfg jHUQ cd TFs
(3JQHjI OjfjIs
Keywords: (3GdOjfs